Assessment of genetically modified oilseed rape GT73 for placing on the market of isolated seed protein for food under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐026/2). (4th November 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Genetically modified oilseed rape GT73 was developed to confer herbicide tolerance; this property was achieved by introducing the single insert containing one copy of goxv247 and the CP4 epsps expression cassettes. The scope of the application EFSA‐GMO‐RX‐026/2 is for the modification of the terms of the authorisation regarding the placing on the market of isolated seed protein from oilseed rape GT73 for food. Considering previous opinions on this event of the GMO Panel, the molecular characterisation data do not identify issues requiring additional food safety assessment. Based on previous assessments, no biologically relevant differences were identified in the compositional, agronomic and phenotypic characteristics of oilseed rape GT73 compared with its conventional counterpart, except for the newly expressed proteins. No new agronomic, phenotypic and compositional data in support of the comparative analysis were considered necessary in the context of this application. The GMO Panel did not identify indications of safety concern regarding toxicity, allergenicity or adjuvanticity related to the presence of the newly expressed proteins CP4 EPSPS and GOXv247 in oilseed rape GT73. Therefore, the GMO Panel concludes that in the context of this application, the consumption of oilseed rape GT73 does not represent any nutritional concern and is as safe as the conventional counterpart. No post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable oilseed rape GT73 into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of oilseed rape GT73. The GMO Panel concludes that oilseed rape GT73 is as safe as its conventional counterpart with respect to potential effects on human and animal health and the environment. These conclusions also apply to the placing on the food market of isolated seed protein produced from oilseed rape GT73.